Warlords in Africa : a comparative study of Jonas Savimbi and Farah Aideed - Lawack, Marvin Sylvester (Stellenbosch : Stellenbosch University, 2008)
Thesis (MA (Political Science. International Studies))--Stellenbosch University, 2008.